Near-death experiences between science and prejudice - Facco, Enrico; Agrillo, Christian (Frontiers in Human Neuroscience, 2012)
Science exists to refute dogmas; nevertheless, dogmas may be introduced when undemonstrated scientific axioms lead us to reject facts incompatible with them. Several studies have proposed psychobiological interpretations of near-death experiences (NDEs), claiming that NDEs are a byproduct of brain functions gone awry; however, relevant facts incompatible with the ruling physicalist and reductionist stance have been often neglected. The awkward transcendent look of NDEs has deep epistemological implications, which call for: a) keeping a rigorously neutral position, neither accepting nor refusing anything a priori; and b) distinguishing facts from speculations and fallacies. Most available psychobiological interpretations remain so far speculations to be demonstrated, while brain disorders and/or drug administration in critical patients yield a well-known delirium in intensive care and anesthesia, the phenomenology of which is different from NDEs. Facts can be only true or false, never paranormal. In this sense, they cannot be refused a priori even when they appear implausible with respect to our current knowledge: any other stance implies the risk of turning knowledge into dogma and the adopted paradigm into a sort of theology.